2013
DOI: 10.1080/10962247.2013.832712
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor fine and ultrafine particle measurements at six bus stops with smoking on two California arterial highways—Results of a pilot study

Abstract: As indoor smoking bans have become widely adopted, some U.S. communities are considering restricting smoking outdoors, creating a need for measurements of air pollution near smokers outdoors. Personal exposure experiments were conducted with four to five participants at six sidewalk bus stops located 1.5-3.3 m from the curb of two heavily traveled California arterial highways with 3300-5100 vehicles per hour. At each bus stop, a smoker in the group smoked a cigarette. Gravimetrically calibrated continuous moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(63 reference statements)
0
11
0
2
Order By: Relevance
“…While the magnitude of exposure varied, in each one of the four experiments, the measured concentration level was lower for the person 1.0 m downwind than for the person 0.5 m away. In a companion field study of six sidewalk bus stops carried out on a major highway, three non‐smokers wearing the same SidePak personal monitors sat on the waiting bench alongside a smoker (Ott et al., ). The average of the PM 2.5 exposure of the three non‐smokers during the smoking period showed a decrease with distance from the smoker, ranging from 59 μg/m 3 at 0.5 m to 40 μg/m 3 at 1.0 m to 28 μg/m 3 at 1.5 m.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the magnitude of exposure varied, in each one of the four experiments, the measured concentration level was lower for the person 1.0 m downwind than for the person 0.5 m away. In a companion field study of six sidewalk bus stops carried out on a major highway, three non‐smokers wearing the same SidePak personal monitors sat on the waiting bench alongside a smoker (Ott et al., ). The average of the PM 2.5 exposure of the three non‐smokers during the smoking period showed a decrease with distance from the smoker, ranging from 59 μg/m 3 at 0.5 m to 40 μg/m 3 at 1.0 m to 28 μg/m 3 at 1.5 m.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the indoor results with similar outdoor experiments, two types of outdoor experiments were performed in the vicinity of Home #1 in Redwood City, CA: (i) sitting at an outdoor table (patio, restaurant, and picnic table) or a park bench; and (ii) sitting at a bus stop on a busy highway. The eight experiments at a bus stop on a busy highway are discussed in a separate paper (Ott et al., ), because in those experiments, two sources were compared (cigarettes and motor vehicle emissions) and we also measured ultrafine particle concentrations and traffic volume simultaneously with the PM 2.5 concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings enforce the results of a recent study, where researchers depicted the exposure levels to fine and ultrafine particles (UFP) by a bus stop, in close proximity of a smoker. PM 2.5 and UFP concentrations were 16–35 and 6.2 times higher than the background concentrations due to cars and trucks on an adjacent arterial highway [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acevedo-Bolton et al (2013) reported in a study of indoor measurements that a nonsmoker sitting within 1 m of a burning cigarette was exposed to over 160 mg/m 3 during the smoking period. In outdoor environments, a strong "proximity effect" of the smoker was observed at bus stops (Ott et al, 2014). The mean PM 2.5 personal exposures of nonsmokers at distances 0.5, 1.0, and 1.5 m from the smoker were 59, 40, and 28 mg/m 3 , respectively, compared with a background level of 1.7 mg/m 3 .…”
Section: Discussionmentioning
confidence: 96%